The Study of Genetics Literacy and Genetics Attitude on Topic of DNA Technology for Grade 10 Students by Context-based Learning Approach - Jiarawattanakorn, Nichapa; Saengsuwan, Arunee (Journal of Inclusive and Innovative Education, 2023)
This research aims to study genetics literacy and genetics attitudes of students on the topic of DNA technology by context-based learning in the situation of the COVID-19 pandemic. The target group consisted of 30 students in grade 10. This research was mixed methods of qualitative and quantitative research. It was used to study the level of genetics literacy and genetics attitudes. The mission sheets during class and genetics literacy assessment form after all lesson plans were analyzed by qualitative content analysis and quantitative method. In addition, qualitative data were also collected from interpretation of the work by using mission sheets, diaries, and semi-structured interviews. Quantitative data were collected from the genetics attitude scale before and after the study. The quantitative data were analyzed by mean, frequency and percentage. The result was found that after learning management most students have genetics literacy at high level in all learning lesson plans. These shown that context-based learning improve students to high level of genetics literacy. The study of genetics attitudes was found that before studying the students had a moderate genetics attitudes, and after studying the students had a good genetics attitudes. These shown that the context-based learning improves students' genetics attitudes.